Effects of flow velocity on water quality and ammonia excretion in recirculating aquaculture system culturing juvenile largemouth bass (Micropterus salmoides) - Xiao, Runguo; Wang, Ganxiang; Chen, Zhenlei; Ye, Zhangying; Zhu, Songming; Ding, Xueyan; Zhou, Fan; Guo, Jianlin; Zhao, Jian (International Journal of Agricultural and Biological Engineering, 2022)
Flow velocity plays an important role in recirculating aquaculture systems (RAS) and the growing practice of culturing juvenile largemouth bass (Micropterus salmoides). In this study, the effects of flow velocity on the water quality as well as the ammonia excretion were discussed from the perspective of actual production, and a polynomial model of ammonia nitrogen excretion was established, using the juvenile largemouth bass. Results showed that the range of ammonia nitrogen and nitrite nitrogen decreased with flow velocity increasing, while the number and volume share of large particles increased. According to the polynomial model, compared with the medium flow velocity (11 cm/s, 2.45 body length (bl)/s), the ammonia excretion of juvenile largemouth bass at high (18 cm/s, 4.00 bl/s), and low (4 cm/s, 0.90 bl/s) flow velocity changed faster with time, and the excretion rate peaked at the 6th hour after feeding, earlier than that under medium flow velocity. Therefore, it is suggested to increase the flow velocity at the 5th hour after feeding and then decreased it at the 10th hour, to ensure better water quality in RAS culturing juvenile largemouth bass. Keywords: flow velocity, recirculating aquaculture system, juvenile largemouth bass, water quality, ammonia excretion DOI: 10.25165/j.ijabe.20221505.7233 Citation: Xiao R G, Wang G X, Chen Z L, Ye Z Y, Zhu S M, Ding X Y, et al. Effects of flow velocity on water quality and ammonia excretion in recirculating aquaculture system culturing juvenile largemouth bass (Micropterus salmoides). Int J Agric & Biol Eng, 2022; 15(5): 213–218.